2021
DOI: 10.29303/jbt.v20i3.2343
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Diversity of Diatom Class Bacillariophyceae as Bioindictaor of Pollution in the Waters of Tanjung Luar Fish Landing Based

Abstract: Tanjung Luar is coastal water used as a waste disposal area for Fish Landing Based (FLB) activities. However, the condition of the waters with phytoplankton as a bioindicator has never been reporting. This research aims to know Bacillariophyceae in terms of abundance, diversity, and measurement of environmental pollution variables. Methods Sampling at the study location was determined by a systematic random sampling method. Data analysis Bacillariophyceae were determined using formula abundance, diversity inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
1
2
0
8
Order By: Relevance
“…These results are in accordance with what was stated by Barus (2020), that a waters that have a microalgae species diversity index of greater than 2 indicates the waters are not polluted. The water quality of Central Lombok's Mandalika SEZ is still better than the Tanjung Luar Fish Auction Port (FAP) waters which are classified as moderately polluted (Audah et al, 2020). The index value of microalgae species diversity in the waters of the Mandalika SEZ was also higher than the species diversity index of the class Bacillariophyceae in the waters of Klui Beach, West Lombok, which was 2.37, as reported by Hadi et al (2022).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…These results are in accordance with what was stated by Barus (2020), that a waters that have a microalgae species diversity index of greater than 2 indicates the waters are not polluted. The water quality of Central Lombok's Mandalika SEZ is still better than the Tanjung Luar Fish Auction Port (FAP) waters which are classified as moderately polluted (Audah et al, 2020). The index value of microalgae species diversity in the waters of the Mandalika SEZ was also higher than the species diversity index of the class Bacillariophyceae in the waters of Klui Beach, West Lombok, which was 2.37, as reported by Hadi et al (2022).…”
Section: Resultsmentioning
confidence: 66%
“…Diatom genus Chaetoceros reported to be abundonce componen of marine phytoplankton which has large number of species and very difficult to identify (Hernandez-Becerril, 1996). Genus Chaetoceros, was also reported to has more species than others genera in some coastal waters of Lombok Island, such as: in the waters of Lembar Harbour West Lombok (Japa, 2000), in the coastal waters of Sambelia East Lombok (Japa dan Suripto, 2003), coastal waters of Mataram City (Japa dan , and in the waters of fish santuary Gili Ranggo Serewe Bay East Lombok , and in the waters of fish landing based Tanjung Luar East Lombok (Audah et al, 2020). Padang et al (2020) also reported that the community of mikroalgae in the coastal waters of Brokoli Island was dominated by diatom genus Chaetoceros.…”
Section: Resultsmentioning
confidence: 99%
“…Spesies Bacillariophyceae yang ditemukan di perairan Pantai Klui terdiri dari 48 spesies, 28 genus dan 17 ordo. Jumlah spesies ini lebih beragam dibandingkan Pantai Jeranjang yakni 26 spesies (Nurlaelatun et al, 2018) dan 27 spesies di perairan PPI Tanjung Luar (Audah et al, 2020). Namun, lebih rendah dibandingkan 75 spesies yang ditemukan di Gili Sulat (Aini et al, 2018).…”
Section: Komposisi Bacillariophyceaeunclassified
“…Indeks keanekaragaman spesies (H') Bacillairophyceae Pantai Klui berkisar 2,04-2,61 (Gambar 6). Kisaran ini lebih tinggi dibanding Pantai Jeranjang yang berkisar 1,25-1,37 (Nurlaelatun et al, 2018) dan perairan PPI Tanjung Luar dengan kisaran 1,858-2,599 (Audah et al, 2020). Indeks keanekaragaman spesies tertinggi pada titik sampling II karena memiliki kelimpahan spesies tinggi dan nilai pH yang cukup tinggi mengindikasikan hasil dari fotosintesis.…”
Section: Indeks Komunitas Bacillariophyceaeunclassified
See 1 more Smart Citation